Offshore wind turbines reliability, availability and maintenance - Tavner, Peter (The Institution of Engineering and Technology, 2012)
The development of offshore wind power has become a pressing modern energy issue in which the UK is taking a major part, driven by the need to find new electrical power sources, avoiding the use of fossil fuels, in the knowledge of the extensive wind resource available around our islands and the fact that the environmental impact of offshore wind farms is likely to be low. This book intends to address these issues head-on and demonstrate clearly to manufacturers, developers and operators the facts and figures of wind turbine operation and maintenance in the inclement offshore environment, recommending how maintenance should be done to achieve low life-cycle costs.